Awareness of infertility among men and women in Kuantan - Md Isa, Muhammad Lokman (IIUM PRESS, 2024)
Infertility, the incapability to conceive after a year of unprotected intercourse, is a growing concern in Malaysia, where total fertility rates have been declining for decades. This research book provides an exploration of the various factors contributing to infertility and offers potential solutions to tackle this increasing issue. For instance, the relation between obesity and male infertility is explored, disclosing how hormonal imbalances due to excess weight can impair sperm production. Additionally, female infertility is examined, with a focus on the impact of irregular menstrual cycles and conditions like polycystic ovary syndrome (PCOS) on complicating conception. Male infertility is further discussed with an emphasis on the societal stigma that often prevents men from seeking help. The book highlights the importance of overcoming this shame and encourages men to educate themselves about potential treatments. The use of traditional, complementary, and alternative medicines (TCAM) among women seeking infertility treatment is also explored, with a focus on the need for professional guidance to ensure harmless and effective use. The possible dangers linked with manhood supplements, including the misapplication of aphrodisiacs like sildenafil (Viagra), are addressed, emphasising the seriousness of health consultation. The book also covers community awareness of in vitro fertilisation (IVF), a promising technology that offers hope to many couples. As a comprehensive resource, this book is invaluable for developing educational programs on infertility. It aims to destigmatise the issue and reassures couples to seek aid from authorised healthcare providers.